Communication Strategy In Supporting State Defense Policy - Santoso, Totok Imam (Ikatan Sarjana Komunikasi Indonesia, 2025)
Currently, strategic communication in supporting national defense policy faces increasingly complex challenges amid geopolitical dynamics, technological developments, and changing patterns of security threats. In the digital era, the government and defense institutions in Indonesia need to utilize information technology to effectively convey policies to the public, while building public trust in the country's defense strategy. In reality, coordination between institutions is still a major challenge, especially in ensuring the integration of messages and synergy of cross-sector communication. In addition, the rampant disinformation and digital propaganda also threaten national security stability, thus requiring strategic efforts to counter negative narratives that can weaken support for defense policies. The purpose of this study is to analyze and identify the role of strategic communication in supporting the implementation of national defense policies, with a focus on the effectiveness of information delivery, coordination between stakeholders, and mobilization of public support. The theory used is Paul Argenti (2007), In his book Strategic Corporate Communication, Argenti states that strategic communication is an organization's effort to convey messages effectively to various stakeholders. The method used is a literature study by reviewing, analyzing, and synthesizing various relevant literature sources. The results achieved are found several indicators to realize Strategic Communication in supporting the National Defense policy is by integrating Communication Adaptability, Inter-Institutional Coordination, Effectiveness of Communication Channels and Public Participation and Involvement so that strategic communication can be an effective tool in strengthening the legitimacy and implementation of national defense policy.